Tracer Film Growth Study of the Corrosion of Magnesium Alloys AZ31B and ZE10A in 0.01% NaCl Solution. Issue 7 (25th May 2017) - Brady, M. P.; Fayek, M.; Leonard, D. N; Meyer, H. M.; Thomson, J. K.; Anovitz, L. M.; Rother, G.; Song, G.-L.; Davis, B.
Abstract : A sequential isotopic tracer study of corrosion film growth for Mg-3Al-1Zn-0.25Mn (AZ31B) and Mg-1.2Zn-0.25Zr-<0.5Nd (ZE10A) was conducted by 4 h immersion in H2 18 O or D2 16 O, followed by a 20 h immersion in a 0.01 wt% NaCl H2 18 O or D2 16 O solution. Sputter depth profiles were obtained for 16 O, 18 O, H, and D using secondary ion mass spectrometry (SIMS). Compared to the previous tracer study for these alloys in salt-free water, the addition of 0.01 wt% NaCl resulted in a transition from oxygen inward-dominated film growth to a component of mixed inward/outward film growth for both alloys. The hydrogen tracer behavior remained inward growing for AZ31B, and short-circuit, inward growing for ZE10A, in both pure water and in 0.01 wt% NaCl solution, with extensive penetration of D beyond the film and into the underlying alloy also observed for ZE10A. Analysis of the films by X-ray photoelectron spectroscopy (XPS) and cross-section scanning transmission electron microscopy (STEM) indicated intermixed Mg(OH)2 and MgO, with the relative fraction of Mg(OH)2 peaking near the center of the film. These findings suggest a decoupled film growth mechanism, with initial formation of oxide followed by NaCl-accelerated conversion to hydroxide, likely by both solid-state and dissolution-precipitation processes.